Bridging the Gap: Exploring the Unique Transition From Home, School or College Into University - Joanne Deborah Worsley; Paula Harrison; Rhiannon Corcoran (Frontiers Media S.A., 2021)
Although previous research has shown that psychological distress increases on entering university, little is known about first-year student perspectives on the stressors in university environments, and what measures might better support student mental health and well-being during the transition period. The present research seeks to bridge this gap by exploring the unique transition period from home, school or college into university in order to identify aspects of the university experience (teaching, curriculum, support services, accommodation) that could be adapted to better support student mental health and well-being. Eight focus groups were conducted across two higher education institutions in North West England. Focus group data were thematically analyzed. Four overarching themes were identified: "Tackling multiple challenges"; "The preparatory role of schools and colleges"; "University staff and services: Feeling supported/unsupported"; and "Friendships." Although pressure to perform academically whilst fulfilling the stereotypical student life is keenly felt during the transition period, many students conceal their struggles from family and friends. Living beyond their familiar support structures often leaves students in need of compassionate humans to turn to for support or advice, especially as many keep their struggles hidden. Large-group teaching settings stifle social connection and leave students feeling lonely. Loneliness was also experienced within accommodation environments. Providing increased opportunities for connection within living and learning environments would enable young people to build and strengthen relationships with fellow students and staff. As supportive environments foster a sense of belonging and community, universities should ensure that students feel supported by staff and peers whilst they acclimatize to multiple new challenges.